213 5-Aminolevulinic Acid for Enhanced Surgical Visualization of High-Grade Gliomas: A Prospective, Multicenter Study. (1st April 2022) - Schupper, Alexander J.; Baron, Rebecca; Cheung, William; Rodriguez, Jessica; Kalkanis, Steven N.; Chohan, Mohammad; Nahed, Brian V.; Zacharia, Brad E.; Jensen, Randy L.; Olsen, Jeffrey; Sherman, Jonathan; Prince, Gabrielle; et al.
Abstract : INTRODUCTION: Greater extent of resection is associated with longer overall survival in patients with high grade gliomas (HGG). 5-aminolevulinic acid (5-ALA) can increase EOR by improving intraoperative visualization of contrast-enhancing tumor during fluorescence-guided surgery (FGS). 5-ALA is converted by glioma cells into protoporphyrin IX (PPIX), which fluoresces under blue light. 5-ALA has been available for use in Europe since 2010, but only recently gained FDA approval as an intraoperative agent for HGG tissue. METHODS: This single-arm, prospective study included adults aged 18-80 with Karnofsky performance status (KPS)>60 and an MRI diagnosis of suspected new or recurrent resectable HGG. Intraoperatively, 3-5 samples per tumor were taken and their fluorescence status recorded by the surgeon. Patients were followed for six weeks postoperatively for adverse events, changes in the neurological exam, and KPS. We performed multivariate analyses of the outcomes of KPS decline, EOR, and residual enhancing tumor volume to identify predictive patient and intraoperative variables. RESULTS: Sixty-nine patients underwent 5-ALA FGS, providing 275 tumor samples for analysis. PPIX fluorescence had a sensitivity of 96.5%, specificity of 29.4%, positive predictive value (PPV) for HGG of 95.4%, and diagnostic accuracy of 92.4%. Drug-related adverse events occurred at a rate of 22%. Serious adverse events occurred at a rate of 4.3%. There were 2 unrelated deaths. KPS was significantly lower at 48 hours and 2 weeks, but was not different at 6 weeks postoperatively. Complete resection of enhancing tumor occurred in 51.9% of patients. Smaller preoperative tumor volume and use of intraoperative MRI predicted lower residual tumor volume. CONCLUSION: PPIX fluorescence, as judged by the surgeon, has a high sensitivity and PPV for HGG. 5-ALA was well-tolerated, and its application by trained surgeons in FGS for HGGs was not associated with any excess neurological morbidity.